Isolation and Characterization of Pistil Predominant Genes from Tomato - Choong, Chieh Wean (2004)
The tomato is an economically and nutritionally important crop that has been extensively used as a research model system to study plant development. In this study, genes predominantly expressed in the pistil were identified and isolated in order to develop an understanding of pistil development and function. Since there have been several studies done in the past examining pistil development, many genes have been isolated and identified. As it became progressively more difficult to identify new genes, alternative approaches have to be employed. In this study, Suppression Subtractive Hybridization (SSH) was used to isolate and identify novel genes predominantly expressed in the pistil. From a pistil subtraction cDNA library, 550 clones were isolated and analyzed where 32.5 % of the genes were found to be predominantly expressed in the pistil through reverse northern screening. All the putative pistil predominant genes were sequenced and 75 independent sequences were found, 42 which had no homology to any known genes from the database and thus appear to encode novel proteins. A collection of genes related to metabolism,photosynthesis and transcription suggest that during anthesis, tomato pistils are more biologically active than other floral organs. Some of these tomato pistil predominant genes included extensin-like protein, ribosomal protein L13 and L13E, sterol-Cmethyltransferase and protein kinase C inhibitor-like protein. Two clones, namely LePiHAT and LePiXTH, were screened for their full-length coding sequences from a pistil cDNA library. LePiHAT was found to be 90 % similar to histone acetyltransferase (HAT) from Arabidopsis thaliana while LePiXTH was 88 % similar to xyloglucan endotransglycosylase/hydrolase (XTH) from A. thaliana. LePiHAT was predominantly expressed in pistils but was also expressed in young stamens, sepals, petals, floral meristems and leaves at lower levels. It was postulated that LePiHAT might be involved in active chromatin remodelling in the pistil. LePiXTH on the other hand was upregulated in young and mature pistils, young stamens and in floral meristems but much lower levels were also detected in the petals, sepals and leaves. Its expression level was highest in floral meristems, followed by vegetative meristems and mature pistils. Its predominant expression in floral meristems, coupled with its localized expression in flower buds suggests its role in floral growth and differentiation. The expression level of LePiXTH in stamens decreased before anthesis but in mature pistils, it was localized in the transmitting tissue that led into the ovary that acts as a channel for pollen tube growth during fertilization. This suggests its role in aiding fertilization through cell walls reconstruction (xyloglucans molecular grafting). The expression level of LePiXTH increased in young fruitlets after anthesis but was not detected in ripe fruit, indicating a possible function in fruit development but not in fruit ripening.